Breeding on the Extreme Edge: Modulation of the Adrenocortical Response to Acute Stress in Two High Arctic Passerines. - Romero, L. Michael.; Walker, Brian G., 1967-; Meddle, Simone L.; Landys, Mėta M., 1973-; Reneerkens, Jeroen.; Wingfield, John C., 1948- (Tufts University. Tisch Library., 2016)
Arctic weather in spring is unpredictable and can also be extreme, so Arctic-breeding birds must be ﬂexible in their breeding to deal with such variability. Unpredictability in weather conditions will only intensify with climate change and this in turn could affect reproductive capability of migratory birds. Adjustments to coping strategies are therefore crucial, so here we examined the plasticity of the adrenocorticotropic stress response in two Arctic songbird species—the snow bunting(Plectrophenax nivalis) and Lapland longspur (Calcarius lapponicus)—breeding in northwest Greenland. Across the breeding season, the stress response was strongest at arrival and least robust during molt in male snow buntings. Snow bunting females had higher baseline but similar stress-induced corticosterone levels compared to males. Modiﬁcation of the stress response was not due to adrenal insensitivity, but likely regulated at the anterior pituitary gland. Compared to independent nestlings and adult snow buntings, parental-dependent chicks had a more robust stress response. For Lapland longspurs, baseline corticosterone was highest at arrival in both male and females, and arriving males displayed a higher stress response compared to arriving females. Comparison of male corticosterone proﬁles collected at arrival in Greenland (76°N) and Alaska (67-71°N;) reveal that both species have higher stress responses at the more northern location. Flexibility in the stress response may be typical for birds nesting at the leading edges of their range and this ability will become more relevant as global climate change results in major shifts of breeding habitat and phenology for migratory birds.